Latinos in the media: an evolving panorama of American television - Lins, Marcella (Brazilian Journal of Latin American Studies, 2023)
In Latino TV: A History, Professor Mary Beltrán provides a historical overview of American television, highlighting the various changes that have occurred in the industry in terms of the representation of Hispanic characters, the relationship of the Hispanic population residing in the United States with mainstream media, and the importance of community members as producers and content creators. Through the analysis of specific episodes, promotional materials, and critical reviews disseminated in society at different times - in addition to conducting interviews with industry professionals - Beltrán demonstrates how cultural norms and industry paradigms compose representation patterns, according to the period in which they are produced. Each chapter of the book covers a different decade, from the 1950s to the 2010s. In this new decade that begins, 24% of the television audience among young adults is of Latino heritage. Given this scenario, Latino TV: A History is essential to understanding how the industry is organized to serve this important consumer market.